SOC 2016 - Witt, John (New York, NY : McGraw Hill, 2016)
A tool that develops students' sociological imaginations by placing them in provocative scenarios where they must analyze various sources and determine a solution. With McGraw-Hill's digital tools, it helps you to focus on what you do best-teaching.
The sociological imagination -- Sociological research -- Culture -- Socialization -- Social structure and interaction -- Deviance -- Families -- Education and religion -- Economy and politics -- Social class -- Global inequity -- Gender and sexuality -- Race and ethnicity -- Population, health, and environment -- Social change
Includes bibliographical references and indexes.
ESS
STS International
Keywords: Sociology Textbooks; Sociology Research; Sociology; Economics; Textbooks